Analysis of seasonal changes in reproductive organs from Icelandic harbour porpoises ( Phocoena phocoena ) - Sverrir Daníel Halldórsson; Gísli Arnór Víkingsson (NAMMCO Scientific Publications, 2003)
In this study, we analyse some aspects of the macro- and microscopical appearance of gonads of harbour porpoises (Phocoena phocoena) from Icelandic coastal waters. Sampling of animals bycaught in gillnets took place in the years 1991 to 1997 and covered the months from September to June. The differences in diameter of seminiferous tubules between samples from the peripheral and central parts of the testis indicate that histological changes associated with maturity begin in the core of the testis. The average tubule diameter was 49, 78 and 118 μm in immature, pubertal and mature animals respectively. The tubule size increased from 55 to 95 μm, coinciding with combined testis weight of 75 to 150 g, indicating the onset of puberty within this range of tubule size and testis weight. The estimated average diameter of tubules when an animal reaches maturity is 82.2 μm or 86.15 μm depending on the method used. The diameter of seminiferous tubules of mature and pubertal animals varies seasonally with a steady increase in the spring. However, lack of samples after mid-June makes estimation of the exact timing of mating impossible. In females, the follicle size of mature and immature animals of age 2 years and older shows seasonalvariation, increasing in late winter or spring. The corpus luteum increases in size during the late pregnancy. The average size of the corpus albicans as a function of the total number of corpora albicantia for each animal, diminishes following the logarithmic equation y = 4.49 – 0.447 · lnx (y = corpus size, x = number of corpora albicantia) but apparently they never disappear completely from the ovary. Ovarian activity was almost confined to the left ovary. Our results indicate parturition and copulation in the summer months from late June to August.